Madeline's Christmas - Bemelmans, Ludwig, 1898-1962. (New York, N.Y., U.S.A. : Viking Kestrel, 1985)
With everyone else sick in bed with a cold on Christmas eve, it is up to Madeline to run the school and she finds a remarkable helper in a rug-selling magician.
Booklist, October 2007.
Horn Book, January 1998.
Bulletin (Center for Children's books), January 2000.
Booklist.
Horn Book.
Bulletin (Center for Children's books).
Keywords: Christmas -- Fiction; Magicians -- Fiction; Stories in rhyme; Christmas -- Fiction; Christmas -- Fiction; Magicians -- Fiction; Stories in rhyme